The Effect of Green Finance on Firm Value with Profitability as a Mediating Variable in Infrastructure Sector Companies - Ningsi, Adita Asma; Bailusy, Muhsin N; Rusandry, Rusandry (IJBLE Scientific Publications Community Inc., 2025)
This study aims to determine and analyze the effect of green finance on firm value with profitability as a mediating variable. This study has a total sample of 16 companies with a purposive sampling technique as a sampling method. The type of data used is secondary data obtained from annual reports, sustainability reports, and company financial reports for four consecutive years. The data analysis method in this study uses Structural Equation Modeling Partial Least Squares (SEM-PLS), and data processing techniques using SmartPLS 4.0 software assistance. The results of this study indicate that green finance affects firm value, green finance affects profitability, profitability affects firm value, and profitability cannot mediate the effect of green finance on firm value